About the succession in the royal family. Literary image of disability in the historical and legal context (Joe Abercrombie Half a King from the Shattered Sea series) - Bolińska, Marta; Zieliński, Patryk (EDUsfera. Ewa Jurczyk-Romanowska, 2020)
The article presents the issue of disability from the literary and legal perspective. The authors take into consideration the issue of disability as a social phenomenon, which is an inseparable element of every environment and culture, as well as the subject of compelling research. An important thread of the article is the transformation of the perception of disability perception throughout the centuries. Joe Abercrombie’s Shattered Sea trilogy serves as a concrete example of its presence. The sketch also revolves around the issue of changes in the perception and treatment of people with disabilities, as well as the introduction of regulations and social education which are to serve as means to provide people with disabilities with equal opportunities in order to function in the society.
Keywords: law; disability; history; young readers novel; literary cycle